GCC Countries : From Oil Dependence to Diversification - Iqbal, Zubair (Pamphlet Series; Pamphlet Series, No., 2003)
This paper presents an overview of the unprecedented economic and social transformation witnessed by the member countries of the Cooperation Council of the Arab States of the Gulf (GCC)-Bahrain, Kuwait, Oman, Qatar, Saudi Arabia, and the United Arab Emirates-over the last three decades.